Management Control System in Islamic Microfinance Institution: A Case Study of BMT Owned by Pesantren in Pamekasan - Fitria, Maulidah; RF, Rahayu Dewi Zakiyah; Syaifullah, Moh (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study explores the design and implementation of Management Control Systems (MCS) in Islamic microfinance institutions, focusing on Baitul Maal wat Tamwil (BMT) owned by Islamic boarding schools (pesantren) in Pamekasan. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis to gain insights into how MCS operates in a unique religious and cultural context. The analysis is guided by the Merchant and Van der Stede framework, which categorizes control into results control, action control, personnel control, and cultural control. Findings reveal that BMTs within pesantren emphasize cultural and personnel controls rooted in Islamic values and pesantren traditions, while results and action controls are adapted to balance both financial performance and socio-religious objectives. A unique finding is that employee recruitment often involves performing shalat istikharah (prayer for guidance) by the management or kyai (religious leader) before finalizing hiring decisions, reflecting a deep integration of spiritual values in personnel management. This study contributes to the literature on management control systems by highlighting how religious-based organizations integrate spiritual and economic goals in their management practices. It also provides practical implications for improving governance and accountability in Islamic microfinance institutions.